Self-consistent solitons for vacuum decay in radiatively generated potentials - Garbrecht, Björn; Millington, Peter (American Physical Society, 2015)
We use a Green’s function approach in order to develop a method for calculating the tunneling rate between radiatively generated nondegenerate vacua. We apply this to a model that exhibits spontaneous symmetry breaking via the Coleman-Weinberg mechanism, where we determine the self-consistent tunneling configuration and illustrate the impact of gradient effects that arise from accounting for the underlying space-time inhomogeneity.